Seminar on Digital Marketing Media Promotion of UMKM Products for Up-Branding and Sales - Zed, Etty Zuliawati; Amanda, Firly; Putri, Tahani Destiani Solihati; Naftalie, Bellatasya; Sari, Santi Fitria (Indonesian Journal of Society Development, 2024)
Indonesia is one of the drivers of Micro, Small and Medium Enterprises (MSMEs) which have a good impact on the people's economy, which often faces several things, namely Partners do not understand Digital Marketing as a promotional medium for business owners and Partners do not understand Up-Branding for their business so that it will have an impact on the progress of their partners because many competitors already have branding on their business. The aim of this service is to provide MSME actors with an understanding of how potential digital marketing tools are as promotional media, which include: Search Engine Marketing (SEM), Content Marketing, Social Media Marketing and Advertising on the Internet, and providing counseling regarding strategies and methods. using various tools available on digital channels, Search Engine Optimization (SEO. The implementation method used is by conducting seminars/training